Impaired mental health status in patients with chronic kidney disease is associated with estimated glomerular filtration rate decline. Issue 9 (29th April 2019) - Onishi, Yasuhiro; Uchida, Haruhito A; Takeuchi, Hidemi; Kakio, Yuki; Sugiyama, Hitoshi; Wada, Jun; Shimada, Noriaki; Tokumasu, Hironobu; Fukushima, Masaki; Asano, Kenichiro
ABSTRACT: Aim: Deteriorated health‐related quality of life (HRQOL) is associated with increased risk for death in both chronic kidney disease (CKD) and end‐stage renal disease (ESRD) patients; however, the impact of HRQOL on CKD progression is not well investigated. Methods: We aimed to evaluate the association between HRQOL and CKD progression in Japanese patients with CKD. One hundred and three outpatients who visited the department of nephrology at our hospital (mean estimated glomerular filtration rate (eGFR); 32.1 ± 11.2 mL/min per 1.73 m 2 ) between April 2007 and March 2012 were enrolled in this study. The primary outcome was 30% decline of eGFR or ESRD. We assessed HRQOL of all participants at baseline, including the physical component summary (PCS), the mental component summary (MCS) and the role/social component summary (RCS), using SF‐36. Based on the baseline score of PCS, MCS and RCS, we divided all subjects into two groups by median. Results: We studied 66 men (64.1%) and 37 women aged 61.7 ± 10.0 years old. During approximately 2.5 years of follow‐up period, 59 patients (57.3%) reached 30% eGFR decline or ESRD. Cox regression analyses demonstrated that lower MCS score was significantly associated with CKD progression (hazard ratio (HR) = 1.83, 95% CI = 1.04–3.21, P = 0.035), but that lower PCS score and RCS score were not (HR = 0.70, 95% CI = 0.39–1.25, P = 0.223; HR = 0.95, 95% CI = 0.54–1.67, P = 0.854, respectively). Conclusion: We found that impaired mental health was associated with CKD progression. The evaluation of the mental health should be performed in the patients with CKD. SUMMARY AT A GLANCE: The authors examined deteriorated health‐related quality of life (HRQOL) using SF‐36 questionnaire. HRQOL of all participants was assessed at baseline, including the physical component summary, the mental component summary and the role/social component summary. They found that impaired mental health was associated with chronic kidney disease (CKD) progression and suggested that evaluation of mental health should be performed in CKD patients.